INNOVATION THAT FITS - Michael D. Lord, Ph.D. , J. Donald deBethizy, Ph.D. Jeffrey D. Wager, M.D. (PEARSON PRENTICE HALL, 2007)
Innovate and die. In evolutionary terms, thatâ€™s usually what happens. Most mutations fail. Few truly new things survive, and even fewer of them thrive. This is just as true in the business world as it is in biology. The record of various innovation fads and fashions during the past few years certainly is consistent with this harsh fact. For much of the past decade, however, management gurus, media, and markets preached a different doctrine. It was a â€œcult of innovation at all costs,â€ an unquestioning, single-minded belief in the power of innovation above all else.1 The risks of innovation seemed passÃ©. 1 1 MAKING SENSE OF INNOVATION FADS AND FASHIONS